ANALISIS PENERAPAN AKUNTANSI SUMBERDAYA MANUSIA DAN DAMPAKNYA TERHADAP LAPORAN KEUANGAN DAN KINERJA PERUSAHAAN - Budi Lesmana; Dedi Karmana; Dadad Zainal Musadad (LPPM POLITEKNIK LP3I BANDUNG, 2021)
Human Resource Accounting currently has not or is not even applied in conventional accounting. This is because the Statement of Financial Accounting Standards is not recognized as an asset. Even so, companies may make other reports where the objective is to recognize human resources as assets that will be presented in the balance sheet of the fixed assets group. The application of conventional accounting that has been carried out by PT PCX can be concluded that the financial performance as measured by the liquidity ratio, solvency, profitability is a different result than if the company applied Human Resource Accounting. Testing is carried out by compiling financial reports in accordance with the Human Resource Accounting concept then conducting financial analysis both on conventional and Human Resource Accounting based financial reports. From the results of this analysis that with the application of Human Resource Accounting company performance is assessed rationally and accurately because by recognizing the human resources as assets. Kata Kunci : Akuntansi Sumber Daya Manusia.